Nanoenzymatic SERS bifunctional detection platform based on recognition competition strategy for ultrasensitive detection of diabetic retinopathy-related biomarkers - Zeng, Binbin; Zong, Xia; Dai, Xinjue; Pan, Lian; Cao, Xiaowei; Lu, Changhua (Frontiers in Bioengineering and Biotechnology, 2025)
Early detection and intervention in diabetic retinopathy (DR) are key to its prevention and treatment. In this study, we propose a surface-enhanced Raman scattering (SERS) bifunctional detection platform based on nanoenzymes catalyzing the tetramethylbenzidine (TMB) reaction, which innovatively introduces an aptamer recognition competition strategy and achieves an ultrasensitive detection of DR associated biomarker (VEGF). The platform employs Au@Pd nanorods (Au@Pd NRs) modified with single-stranded DNA1 (ssDNA1) as nanoenzymatic probes. Arrays of Au trioctahedra (Au TOHs) with surface-modified double-stranded structures, including aptamer strands and single-stranded DNA2 (ssDNA2), were used as capture substrates. When the target protein is present in the solution to be tested, the aptamer specifically recognizes the target protein and detaches from the surface of the capture substrate, exposing ssDNA2 and being recognized and bound by ssDNA1, allowing a large number of nanoenzymatic probes to be bound to the capture substrate, and the assay platform thus possesses excellent POD activity and SERS performance, being able to catalyze the generation of TMB with a strong SERS signal oxTMB. The platform demonstrated high detection performance, completing the assay within 14 min, with a low limit of detection (LOD) of 0.11 pg/mL. It maintained robust clinical performance even in complex serum samples, and the results were consistent with ELISA. This work offers a framework for constructing nanoenzyme-SERS bifunctional detection systems and introduces a new approach for biomarker detection.